The genome of the heartwater agent Ehrlichia ruminantium contains multiple tandem repeats of actively variable copy number - Collins, N.E.; Liebenberg, J.; Villiers, Etienne P. de; Brayton, K.A.; Louw, E.; Pretorius, E.; Faber, F.E.; Heerden, H. van; Josemans, A.; Kleef, M. van; Steyn, H.C.; Strijp, M.F. van; et al. (National Academy of Sciences, 2005)
Heartwater, a tick-borne disease of domestic and wild ruminants, is caused by the intracellular rickettsia Ehrlichia ruminantium (previously known as Cowdria ruminantium). It is a major constraint to livestock production throughout subSaharan Africa, and it threatens to invade the Americas, yet there is no immediate prospect of an effective vaccine. A shotgun genome sequencing project was undertaken in the expectation that access to the complete protein coding repertoire of the organism will facilitate the search for vaccine candidate genes. We report here the complete 1,516,355-bp sequence of the type strain, the stock derived from the South African Welgevonden isolate. Only 62% of the genome is predicted to be coding sequence, encoding 888 proteins and 41 stable RNA species. The most striking feature is the large number of tandemly repeated and duplicated sequences, some of continuously variable copy number, which contributes to the low proportion of coding sequence. These repeats have mediated numerous translocation and inversion events that have resulted in the duplication and truncation of some genes and have also given rise to new genes. There are 32 predicted pseudogenes, most of which are truncated fragments of genes associated with repeats. Rather then being the result of the reductive evolution seen in other intracellular bacteria, these pseudogenes appear to be the product of ongoing sequence duplication events.